Live Streaming and Impulse Buying in Social Commerce: A Comparative Study of TikTok and Shopee with Price Consciousness as a Moderator - Alsya Siti Aenaya; Sulhaini; Baiq Handayani Rinuastuti (CV. Media Digital Publikasi Indonesia, 2025)
The main purpose of this study is to examine the influence of live streaming on impulse buying of local fashion products with price consciousness as a moderation variable on the TikTok and Shopee platforms. The population in this study is young female consumers who shop for local fashion products unintentionally on live streaming social commerce platforms — TikTok and Shopee. The sample in this study amounted to 150 respondents spread across various regions in Indonesia. The results showed that live streaming had a positive and significant effect on impulse buying on both platforms, with a stronger influence on TikTok. In addition, price consciousness has been proven to moderate the influence of live streaming on impulse buying on TikTok, but not significantly on Shopee.